Islam and Syncretism in Java: Reflections on the Thought of Geertz and Woodward (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2021)
This article aims to revisit the concept of Javanese Islam in the thinking of Clifford Geertz and Mark R Woodward. This study is not a comparative study of the two figures but rather a criticism of Geertz's thinking using Woodward's thinking. Geertz stated that Islam in Java is considered a practice that deviates from Islamic values ​​and teachings. Geertz's grouping of religious typology, namely Priyayi, Abangan, and Santri, is also problematic. Priyayi and abangan groups are considered followers of mystical teachings (kejawen), while the santri group adheres to pure Islam. Meanwhile, Woodward explains Javanese Islam with the theory of mystical Islam (Islamic Sufism). Woodward divides it into three essential characteristics: first, to believe in God Almighty, second, to be mystical, and third, to have a syncretic character. According to Woodward, there is only one Javanese religion, and the binding factor is Islam, not Java, as Geertz’s statement.